Causes of acute respiratory failure in patients with small-vessel vasculitis admitted to intensive care units: a multicenter retrospective study - Aude Gibelin (SpringerOpen, 2021)
Abstract Rationale Acute respiratory failure (ARF) in patients admitted to the intensive care unit (ICU) with known or de novo small-vessel vasculitis (Svv) may be secondary to the underlying immune disease or to other causes. Early identification of the cause of ARF is essential to initiate the most appropriate treatment in a timely fashion. Methods A retrospective multicenter study in 10 French ICUs from January 2007 to January 2018 to assess the clinical presentation, main causes and outcome of ARF associated with Svv, and to identify variables associated with non-immune etiology of ARF in patients with known Svv. Results During the study period, 121 patients [62 (50–75) years; 62% male; median SAPSII and SOFA scores 39 (27–52) and 6 (4–8), respectively] were analyzed. An immune cause was identified in 67 (55%), and a non-immune cause in 54 (45%) patients. ARF was associated with several causes in 43% (n  = 52) of cases. The main immune cause was diffuse alveolar hemorrhage (DAH) (n  = 47, 39%), whereas the main non-immune cause was pulmonary infection (n  = 35, 29%). The crude 90-day and 1-year mortality were higher in patients with non-immune ARF, as compared with their counterparts (32% and 38% vs. 15% and 20%, respectively; both p  = 0.03), but was marginally significantly higher after adjusted analysis in a Cox model (p  = 0.053). Among patients with a known Svv (n  = 70), immunosuppression [OR 9.41 (1.52–58.3); p  = 0.016], and a low vasculitis activity score [0.84 (0.77–0.93)] were independently associated with a non-immune cause, after adjustment for the time from disease onset to ARF, time from respiratory symptoms to ICU admission, and severe renal failure. Conclusions An extensive diagnosis workup is mandatory in ARF revealing or complicating Svv. Non-immune causes are involved in 43% of cases, and their short and mid-term prognosis may be poorer than those of immune ARF. Readily identified predictive factors of a non-immune cause could help avoiding unnecessary immunosuppressive therapies.